THE INFLUENCE OF E-COMMERCE ON BUYER INTEREST (STUDY ON STUDENTS OF THE ISLAMIC ECONOMICS STUDY PROGRAM AT IAIN AMBON) - Retno Widia Astuti Retno (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This research is motivated by the increasing competition in online buying and selling activities, particularly among students of the Sharia Economics Study Program, which has influenced consumer buying interest. Businesses and online stores are encouraged to innovate and improve customer satisfaction strategies to sustain consumer engagement in e-commerce platforms. The study aims to examine whether e-commerce has an effect on buying interest and to what extent it influences the buying interest of students in the Sharia Economics Study Program at IAIN Ambon. Data were collected through a questionnaire distributed to 32 respondents who had previously made purchases via e-commerce platforms. The research methodology includes research design, data sources, data collection methods, population and sample, data processing techniques, and quantitative data analysis. The results of the study indicate that e-commerce significantly influences buying interest. This is supported by the t-test result of 9.649 with a significance level of 0.000 (< 0.05), indicating a statistically significant relationship. The coefficient of determination (R²) shows that e-commerce accounts for 74.8% of the variance in buying interest, while the remaining 25.2% is influenced by other variables not examined in this research.